2017
DOI: 10.1002/bit.26437
|View full text |Cite
|
Sign up to set email alerts
|

Cascading effect in bioprocessing—The impact of mild hypothermia on CHO cell behavior and host cell protein composition

Abstract: A major challenge in downstream purification of monoclonal antibodies (mAb) is the removal of host cell proteins (HCPs). Previous studies have shown that cell culture conditions significantly impact the HCP content at harvest. However, it is currently unclear how process conditions affect physiological changes in the host cell population, and how these changes, in turn, cascade down to change the HCP profile. We examined how temperature downshift (TDS) to mild hypothermia affects key upstream performance indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 30 publications
3
39
0
Order By: Relevance
“…Interestingly, cell viability was maintained at high percentages in mild hypothermic bioreactors operated in similar working volume, stirring speed and aeration rate as the control. Cells at 32C appeared to be more robust than the control which is believed to be a result of homeoviscous adaptation of the cell membrane at lower culture temperature [12,13,27].…”
Section: Cell Growthmentioning
confidence: 99%
See 3 more Smart Citations
“…Interestingly, cell viability was maintained at high percentages in mild hypothermic bioreactors operated in similar working volume, stirring speed and aeration rate as the control. Cells at 32C appeared to be more robust than the control which is believed to be a result of homeoviscous adaptation of the cell membrane at lower culture temperature [12,13,27].…”
Section: Cell Growthmentioning
confidence: 99%
“…Furthermore, HCPs such as chaperones and proteases may compromise product quality by promoting product aggregation or fragmentation [8][9][10]. In the past five years, the concept of Quality by Design (QbD) had been employed to understand the impact of upstream culture conditions like cell age, cell culture mode (batch or fed-batch), process duration and culture temperature on HCP profile [11][12][13][14] with an aim to reduce the level of HCPs in downstream feedstock by optimizing cell culture conditions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…With the rise of biosimilars across the globe, process changes are inevitable as biosimilar manufacturers do not have access to the process used by the manufacturer of the innovator product . Researchers have shown that these process changes or manufacturing drifts could influence both the levels of HCPs as well the HCP species finally end up in the biotherapeutic product . Thus, while the criterion of 100 ppm target limit may be satisfied, manufacturers need a deeper understanding of the HCPs present in the product and their impact on the product's safety and efficacy.…”
Section: Discussionmentioning
confidence: 99%